Shaping Citizenship: Dynamic Relations Between the Reified and the Consensual Universes in Defining the “Good Foreign Resident” - Tânia R. Santos; Paula Castro (Journal of Social and Political Psychology, 2023)
A social and political psychology of citizenship can be furthered by the analysis of the values and representations through which citizenship is constructed in the text of laws and reconstructed during implementation and how these (re)constructions best serve some groups. This article views laws as facts from the reified/institutional universe whose texts operate a simplification process by prioritizing certain values from the plurality existent in the consensual universe and sees institutions in charge of law implementation as mediating systems operating re-complexification processes. Using this perspective, it (1) explores how the values and social representations prioritized in Portuguese foreign residency laws exclude/include certain groups and define rights and duties of “the good foreign resident/citizen”; (2) illustrates with interviews with experts from a mediating system (n = 6) the re-complexification of the laws in implementation. It highlights how the “worthiness” of foreign residents in Portugal depends upon three central values (work, study, and investment) keeping, however, some ambiguity of these values in the legal texts. Interviews illustrate how mediating systems re-signify the laws, amplifying the ambiguities by resorting to other values and representations. We discuss how the analysis of the dynamic relation between the reified and the consensual universes contributes to a better understanding of how macro-level factors interact with everyday citizenship.